Analisis Implementasi Enterprise Risk Management dan Transformasi Digital pada PT Bank Mandiri (Persero) Tbk Periode 2021–2025: Pendekatan Studi Kasus - Norbayah Norbayah; Nur Asim; Edo Rahman; Nurlia Nurlia (Lembaga Teewan Journal Solutions, 2026)
Advancements in digital technology have compelled the banking industry to undergo continuous business transformation. This strategic shift aims to improve service quality, optimize operational efficiency, and boost corporate competitiveness. Conversely, digital adaptation also introduces novel risks that require effective mitigation through the framework of Enterprise Risk Management (ERM). This study evaluates the implementation of ERM alongside digital transformation at PT Bank Mandiri (Persero) Tbk from 2021 to 2025, while exploring their correlation with corporate performance. Utilizing data extracted from the annual reports of PT Bank Mandiri (Persero) Tbk spanning 2021–2025, this research employs a descriptive qualitative approach integrated with case study and content analysis methods. The findings demonstrate that Bank Mandiri consistently strengthens all eight pillars of ERM risk dimensions, which include credit, market, liquidity, operational, legal, compliance, strategic, and reputational risks throughout the observation period. Simultaneously, the bank’s digital breakthroughs are executed through key initiatives, namely Livin' by Mandiri, Kopra by Mandiri, Smart Branch, Digital Ecosystem Development, and the Integrated Digital Platform. The synergistic integration between ERM and digital transformation significantly drives corporate performance. This positive impact is evidenced by a substantial surge in net profit, climbing from IDR 28.03 trillion in 2021 to IDR 56.29 trillion in 2025, alongside an asset expansion from IDR 1,726 trillion to IDR 2,830 trillion.